Assessment of supply chain finance adoption among Malaysian manufacturing firms / Mohamad Aznillah Ahmad … [et al.] - Ahmad, Mohamad Aznillah; Pyeman, Jaafar; Ali, Norli; Abdul Rahman, Norsariah (Faculty of Accountancy, 2019)
Malaysian’s manufacturing firms always facing difficulty in getting financial assistance from the financial institution. Despite many financing products available, supply chain finance (SCF) adoption was very lacking. Since SCF is relatively unfamiliar compared to conventional or Islamic financing, the adoption rate was very low. The purpose of this paper is to investigate the determinants of SCF adoption intention in the context of Malaysian manufacturing industries. Using theory of planned behavior (TPB) and technology acceptance model (TAM), it is aimed to explain the effect of knowledge and awareness, cost benefit, business support and reputation as well as Perceived Ease Of Use (PEOU) and Perceived Usefulness (PU), on adoption attitude and intention towards SCF. The study was using a quantitative approach via 1,000 questionnaires distributed to Malaysian’s manufacturing firms, and only 411 were returned. Structural equation modelling using partial least squares approach was then utilized to assess the relationships of all variables. Data has been tested using measurement model while structural model assessment was performed to test the hypotheses. The findings show that knowledge and awareness, cost benefit, reputation, PEOU and PU have positive effect on adoption attitude of Malaysians manufacturing firms towards SCF. Attitude, subjective norm and perceived behavioral control have positive effect on adoption intention, while attitude only mediate knowledge and awareness, cost benefit, reputation and adoption intention. The mediation effect of attitude implies the importance of recommendations and favorable word-of-mouth from the significant ones, such as family members and peers, to make manufacturer willing to try and adopt it. The study contributes to body of knowledge by having an extensive use of TPB with TAM in the context of manufacturing firm in explaining the SCF adoption intention. Given the need to explore new financing product, understanding SCF would contribute to the manufacturing industries and to the Malaysian economy.